STAKEHOLDER DALAM PROSES NEGOSIASI KEBIJAKAN RELOKASI IBUKOTA KECAMATAN: Studi Kasus Kecamatan Batulanteh Kabupaten Sumbawa - , AMRULLAH, S.AP ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Policy issue has been the most difficult problem justified and confronted with either administrative or political an sich reasons